Development of methodology of efficiency estimation of management technology of project-oriented organizations - Timinsky, Alexander; Oberemok, Ivan; Oberemok, Nataliia (Technology audit and production reserves, 2017)
Support for the competitiveness of modern companies is realized through the application of the methodology of project management. The project management subsystem should be harmoniously integrated into the enterprise management system. At the same time, the coordinated operation of the project and operating subsystems should be ensured. The interaction of the project and operating subsystems of the project-oriented enterprise can be realized within the framework of several approaches – the homeostatic approach, the bi-adaptive management approach. To create management systems for project-oriented enterprises that work in concert, it is necessary to evaluate the interaction of management subsystems. The article poses the task of estimation of the interaction between the projects subsystem and operating subsystem of a project-oriented enterprise. The essential parameters of the operating subsystem and project subsystem are divided into ten groups of parameters. In the operating subsystem 28 parameters are allocated, in the project subsystem – 27. A method of combined analytical and expert estimation of the mutual influence of the project and operating subsystems of the project-oriented enterprise (MAEM method) is proposed. The eight steps of the method implementation are described – an analytical estimation of the state of parameters that can be estimated accurately; Selection of candidates for two expert groups (from operating managers and project managers); Determination of competence coefficients of candidates for experts; Identification of experts; Estimation by experts of the interaction between the parameters of the project and operating subsystems; Determination of the most sensitive parameters; Determination of deviations between expert group estimates; Formulation of conclusions. The method is based on expert estimation The strengths, weaknesses of the method, its opportunities and threats are analyzed. The method will allow to create coordinated control systems for project-oriented enterprises.